Complete A-Z biology handbook - Indge, Bill (Hodder And Stoughton London, 2003)
Designed to be invaluable at every stage of A level courses, 'Complete A-Z Handbooks' are focused glossaries which provide straightforward definitions to clarify complex jargon, clear treatment of key concepts and revision lists